Representasi Kekayaan dalam Surah al-Qaṣaṣ ayat 76–82: Pembacaan Tafsir al-Qurṭubī atas Budaya Flexing Remaja Muslim - Tri Yolanda Virli; Mhd. Syahminan; Nur Fadhilah Syam (Yayasan Albahriah Jamiah Indonesia, 2026)
The culture of flexing among Muslim youth in the digital space has developed as an expression of social status based on the display of wealth published through social media, giving rise to a symbolic orientation towards material things as well as a shift in ethical values ​​in interpreting wealth, so that reading the Qur’an becomes important as a normative basis for responding to this phenomenon. The purpose of this study focuses on analyzing the construction of the meaning of wealth in Surah al-Qaṣaṣ verses 76–82 according to al-Qurṭubī and its relevance to contemporary flexing practices. The approach used is qualitative, based on literature studies with the thematic interpretation method (mawḍūʻī), making Tafsir al-Qurṭubī the main reference through textual, thematic, and contextually critical analysis to interpret the relationship between the narrative of Qārūn and modern social phenomena. The study’s findings demonstrate the interpretation of wealth as a moral test that demands a balance between ownership and ethical awareness, where arrogance, ostentation, and denial of the social dimension are positioned as value deviations. In contrast, social responsibility, humility, and a utilitarian orientation become the primary principles. The practice of flexing is understood as transforming the meaning of wealth into a performative symbol that has the potential to obscure the ethical purpose of wealth ownership, thus giving rise to a consumerist and existential culture. The study’s implications emphasize the importance of internalizing the ethical values ​​of the Qur’an in controlling the expression of wealth in the digital space so that it remains oriented towards social welfare.